Workshop Implementasi Bimbingan Dan Konseling Dalam Kurikulum Merdeka Dan Penyusunan Perangkat Pembelajaran (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
A guidance and counseling teacher is a figure who supports the smoothness of the learning process in school. Through their duties, guidance and counseling teachers are required to develop their competencies through innovation and curriculum development. In order to enhance their competencies, a workshop on the implementation of guidance and counseling within the "Merdeka" curriculum and the development of learning materials is conducted. Some of the steps applied in this workshop include distributing questionnaires to assess the understanding of developing learning materials in the "Merdeka" curriculum, analyzing the needs of educators and students, deepening theoretical knowledge, and practicing the development of guidance and counseling learning materials within the "Merdeka" curriculum. This activity is typically attended by guidance and counseling teachers from Junior High Schools in the Ketapang Regency, West Kalimantan Province, and is held at SMP Negeri 3 Ketapang.